Developing Chinese Textbooks to Match Thai Learners’ Identity in Higher Education, Thailand - Wei, Xiaoxia; Weerasawainon, Aeksing (Scholar: Human Sciences, 2019)
This paper aims to develop Chinese textbooks targeting Thai learners by assessing the overall effectiveness of the Chinese textbooks used in the international programs in higher education institutions, Thailand, as well as by analyzing Thai learners’ perceptions toward the textbooks. The three Chinese textbooks being used were analyzed in terms of the amount of grammar, the level of difficulty of grammar, topics, vocabulary and cultural knowledge. One hundred and sixty-nine college students participated in the study to express their attitudes towards the textbooks. The results showed that although the Chinese textbooks target beginners, there was a lack of content consistency. Moreover, there were significant mismatches between the textbooks and the Thai learners’ needs and wants in terms of text topics, cultural knowledge, and real-life application. The researchers, therefore, would like to propose that Chinese textbooks in Thai market should adopt a learner-centered approach to satisfy Thai learners’ identity.